1997
DOI: 10.1023/a:1008256431090
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of five versus eight courses of cisplatin or carboplatin in advanced epithelial ovarian carcinoma

Abstract: There is insufficient evidence at the present time to justify more than five courses of first-line single agent platinum chemotherapy in the management of advanced ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 17 publications
0
62
0
1
Order By: Relevance
“…Comparison of the survival data from our study with that of a matched population of patients with suboptimally debulked, advanced ovarian cancer, all of whom received between five and eight cycles of carboplatin (Lambert et al, 1993(Lambert et al, , 1997, were identical. Therefore, it is plausible that patients in the current study were not disadvantaged by receiving only two cycles of carboplatin.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Comparison of the survival data from our study with that of a matched population of patients with suboptimally debulked, advanced ovarian cancer, all of whom received between five and eight cycles of carboplatin (Lambert et al, 1993(Lambert et al, , 1997, were identical. Therefore, it is plausible that patients in the current study were not disadvantaged by receiving only two cycles of carboplatin.…”
Section: Discussionmentioning
confidence: 89%
“…Survival in the study population is compared in these figures with 3 7 2 2 0 0 0 0 1 3 1 1 Mucositis 0 0 0 0 1 2 1 1 0 0 0 0 Diarrhoea 1 2 1 1 0 0 0 0 2 5 2 1 Alopecia 0 0 0 0 15 37 22 28 18 47 72 50 Thromboembolic event 2 5 2 2 1 2 2 3 0 0 0 0 Haematological Anaemia 1 2 1 1 2 5 2 3 6 16 6 4 Neutropenia 2 5 0 0 2 5 3 4 31 82 88 61 Neutropenic sepsis 2 5 2 2 2 5 2 3 5 13 8 6 Thrombocytopenia 1 2 1 1 0 0 1 1 4 11 5 that of a matched group of patients from two previous North Thames ovary trials and found to be similar (Lambert et al, 1993;Lambert et al, 1997). In this group, all patients had inoperable disease or measurable disease 42 cm at the end of surgery and received between five and eight cycles of carboplatin.…”
Section: Responsementioning
confidence: 91%
See 1 more Smart Citation
“…There have been trials comparing shorter vs longer chemotherapy treatments; overall, there is little scientific evidence that prolonging standard induction chemotherapy offers a survival advantage. 19,20 Newer approaches have included IP interferon-alpha, which has shown activity in patients with low volume chemosensitive disease. 21 Clinical trials are underway to determine the role of other therapies, including interleukins and gene therapy.…”
Section: Autologous Transplantation In Ovarian Cancer ML Donato Et Almentioning
confidence: 99%
“…Most patients diagnosed with more advanced stage disease go on to develop disease recurrence. Much interest has focused on the prevention of disease recurrence in ovarian cancer by manipulating initial treatment via different routes of administration of chemotherapy (ie, intraperitoneal [3]), prolonged courses of initial chemotherapy [4,5], or the use of neoadjuvant chemotherapy before optimal initial debulking surgery [6]. Future strategies might entail the use of biologic therapies after standard chemotherapeutic strategies as consolidation or maintenance following primary treatment.…”
Section: Therapeutic Approaches To Prevent Ovarian Cancer Relapsementioning
confidence: 99%